Cell-Based Versus Enzyme-Linked Immunosorbent Assay for the Detection of Acetylcholine Receptor Antibodies in Chinese Juvenile Myasthenia Gravis - Yan, Chong; Li, Wenhui; Song, Jie; Feng, Xuelin; Xi, Jianying; Lu, Jiahong; Zhou, Shuizhen; Zhao, Chongbo (Pediatric neurology, 2019)
Patients in China with juvenile-onset myasthenia gravis present early, with a high prevalence of purely ocular symptoms, spontaneous remission rates, and low antibody seropositivity. Antibody detection using a cell-based assay has been reported to increase the diagnostic sensitivity in adult-onset myasthenia gravis. However, this method in patients with juvenile-onset myasthenia gravis has not been investigated. Patients with juvenile-onset myasthenia gravis who had not received prednisone or immunosuppressive therapy were recruited between June 2015 and April 2018 at the Huashan Hospital. Clinical information was collected. Serum anti-acetylcholine receptor antibodies were detected via cell-based assay with HEK293T cells expressing acetylcholine receptor subunits and rapsyn. Additionally, the IgG antibody subclass was identified. Eighty-two patients with juvenile-onset myasthenia gravis were enrolled in the current study. Among them, 48 patients were anti-acetylcholine receptor positive (58.5%) and 34 were seronegative (41.5%), as assessed via enzyme-linked immunosorbent assay. Cell-based assay yielded 63 positive subjects (76.8%) and 19 seronegative subjects (23.2%). All the enzyme-linked immunosorbent assay-positive samples showed robust immunofluorescence in the cell-based assay, whereas 15 of 34 enzyme-linked immunosorbent assay-negative patients (44.1%) were found to have low-affinity acetylcholine receptor antibodies. Among all the cell-based assay-positive patients, 41 were positive for both adult and fetal acetylcholine receptor antibodies (50.0%), 18 were found positive for only adult acetylcholine receptor antibodies (21.9%), and four were found to possess only fetal acetylcholine receptor antibodies (4.9%). Fifteen antibody-positive samples underwent subclassification and were confirmed to be IgG1 subclass predominant (n = 15, including eight adult and fetal acetylcholine receptor antibody positive, five only adult acetylcholine receptor antibody positive, and two only fetal acetylcholine receptor antibody positive). There were no significant differences in clinical features among patients with different antibody profiles. The cell-based assay showed increased sensitivity in acetylcholine receptor antibody detection in Chinese patients with juvenile-onset myasthenia gravis, and most cases of Chinese juvenile-onset myasthenia gravis are still acetylcholine receptor autoantibody mediated. Furthermore, the antibodies detected are predominately of the IgG1 subclass.